2016
DOI: 10.1007/s11420-015-9476-2
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Ultrasonography Has Limited Utility in Detection of Postoperative DVT After Primary Total Joint Arthroplasty

Abstract: Background: Duplex ultrasound is routinely used to evaluate suspected deep venous thrombosis after total joint arthroplasty. When there is a clinical suspicion for a pulmonary embolism, a chest angiogram (chest CTA) is concomitantly obtained. Questions/Purposes: Two questions were addressed: First, for the population of patients who receive duplex ultrasound after total joint arthroplasty, what is the rate of positive results? Second, for these patients, how many of these also undergo chest CTA for clinical su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…To date, despite the frequent use of venography and venous duplex for diagnosis of DVT in clinical trials, routine venous duplex and venography screening following THA and TKA is not recommended by the clinical practice guidelines developed by the American Academy of Orthopaedic Surgery (AAOS) and the American College of Chest Physicians (AACP) 1230-1234 .…”
Section: - What Endpoint Should Be Used To Determine the Efficacy Of ...mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, despite the frequent use of venography and venous duplex for diagnosis of DVT in clinical trials, routine venous duplex and venography screening following THA and TKA is not recommended by the clinical practice guidelines developed by the American Academy of Orthopaedic Surgery (AAOS) and the American College of Chest Physicians (AACP) 1230-1234 .…”
Section: - What Endpoint Should Be Used To Determine the Efficacy Of ...mentioning
confidence: 99%
“…Both groups developed similar rates of proximal DVT by day 35 postoperatively (below 9%), questioning the utility of screening ultrasound 1232 . Furthermore, a recent retrospective single-center study found that in patients who underwent total joint arthroplasty and had a duplex ultrasound, only 0.7% of them had a DVT and none of them exhibited clinical symptoms 1234 . Shahi et al, found that the rate of in-patient DVT being diagnosed has decreased significantly during the past decade, likely due to less screening of asymptomatic patients, while the rate of PE development has remained stable 1210 .…”
Section: - What Endpoint Should Be Used To Determine the Efficacy Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, ultrasound, an imaging modality without those burdens, has high rates of missed diagnoses due to low true positive and high false negative rates [47]. In settings where ultrasound is not available, has limited use [48], or is inconclusive, secondary imaging modalities such as CT or MRI venography can provide 3D reconstructed images to estimate thrombus burden; however, standardized protocols for quantification are lacking. Pretest probability assessments such as the Wells and Caprini Scores help stratify risk and guide VTE diagnosis [49,50]; however, they are inconsistently applied and can still lead to missed diagnoses.…”
Section: Diagnostic Developmentmentioning
confidence: 99%